GAMBARAN PERILAKU IBU PETANI DALAM PEMENUHAN GIZI PADA ANAK BALITA DI DESA BANGKO BAKTI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Suharni .; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The first two year  old is a golden period so that the nutritional needs in this period should really be noted to optimize the brain development. A child’s future will be reflected by the nutritional intake in the first 2 years. If the nourishment is good today, the nutritional status will be good too in the next days and if this time, the nutritional needs are not fulfilled, it will be difficult to substitute the missing nutritional needs during the coming.The objective of this study is to describe the behaviors of farmer women in toddlers’ nourishment at Desa Bangko Bakti Sub-district of Bangko Pusako Regency of Rokan Hilir in 2012. This is a descriptive study using a cross sectional study design. The primary data was obtained by giving questionnaire interviews, 24-hour food recalls and food frequencies, the secondary data was obtained from the village head’s office. Sampling was done by purposive sampling with criteria: toddlers taken to the farm by their parents.The results showed that the women who have a good knowledge but have not been able to comply their toddlers’ nutritional needs in terms of 72.7% energy is due to the toddlers would not eat and the mothers would not persuade. The women with moderate knowledge have been able to meet the nutritional needs of their toddlers in case of 73.6% protein is because they provide eggs as a side dish every day. The women who have a good attitude, but have not been able to fulfill their toddlers’ nutritional needs in case of energy are as much as 71.9%.Based on the research, it is suggested to held a counseling about the importance of toddler’s nourishment, especially energy and protein and to the farmer women, it is suggested to be more concerned with the quantities and qualities of food given to their toddlers, they could also consume other kinds of food as the energy sources to substitute the prior foods such as refined flours, sweet potatoes, and sago. Keywords : Behavior, Farmer women, Nourishment, Toddler